"This Research Is Cool": Engaging Youth Experiencing Homelessness in Research on Reproductive and Sexual Health. Issue 5 (1st June 2020) - Begun, Stephanie; Weber, Ariel; Spring, Joshua; Arora, Simran R. A.; Frey, Cressida; Fortin, Alicia
ABSTRACT: Youth experiencing homelessness face myriad barriers and inequities regarding their reproductive and sexual health and rights. Moreover, homeless youth are often characterized as "disaffiliated" and depicted as difficult to engage in research. This study qualitatively explored homeless youths' attitudes, beliefs, and needs regarding reproductive and sexual health, and sought their perspectives on being involved in research on such topics, which are often thought of as "taboo" or sensitive. Youth were enthusiastic about openly discussing such issues, which they deemed as highly relevant to their daily lives. Youth identified that how they were engaged in such research, and having opportunities for longer-term contributions to such efforts, were both important and exciting to them. Future social work and public health research efforts should seek to further disrupt narratives of homeless youth as "disaffiliated" and difficult to engage, and in doing so, develop more creative, participatory, and youth-led opportunities for including this group in reproductive and sexual health research.